Ischemic preconditioning: No influence on maximal sprint acceleration performance - Thompson, K. M. A.; Whinton, A. K.; Ferth, S.; Spriet, L. L.; Burr, J. F. (International Journal of Sports Physiology and Performance, 2018)
Ischemic preconditioning (IPC) was initially developed to protect the myocardium from ischemia through altered cardiocyte metabolism. Because of the observed effects on metabolism and oxygen kinetics, IPC gained interest as a potential ergogenic aid in sports. Limited research evaluating the effects of IPC on maximal short-duration activities has been performed, and of the existing literature, mixed outcomes resulting from intrasubject variation may have clouded the efficacy of this technique for enhancing sprint performance. Therefore, the current study employed a randomized repeated-measures crossover design with IPC, placebo (SHAM), and control conditions while using sprint-trained athletes (N=18) to determine the effect of IPC (3×5-min occlusions, with 5-min reperfusion), concluding 15 min prior to maximal 10-s and 20-m sprinting. A visual analog scale was used in conjunction with the sprint trials to evaluate any possible placebo effect on performance. Despite a "significantly beneficial" perception of the IPC treatment compared with the SHAM trials (P<.001), no changes in sprint performance were observed after either the IPC or SHAM condition over 10 m (IPC Delta < 0.01 [0.02] s, SHAM Delta < 0.01 [0.02] s) or 20 m (IPC Delta=-0.01 [0.03] s, SHAM Delta< 0.01 [0.03] s) compared with control. Thus, an IPC protocol does not improve 10- or 20-m sprint performance in sprint-trained athletes.